Trickle down Registration: Exploring the Lived Experiences of Partners of Persons Registered as a Sexual Offender. Issue 8 (3rd July 2022) - Marsh, Shawn C.; Russell, Kristan N.; Evans, William P.
ABSTRACT: Accessing stigmatized persons for research purposes can be difficult, and accessing their significant others is perhaps even more challenging. We present here our defining moments of recruiting and surveying partners of persons registered as sexual offenders for our research on courtesy stigma. The challenges and successes of our journey are described within the larger hypothesis that close relationships are an important source of social support associated with adjustment and well-being outcomes for people involved in the justice system as well as their families. Ultimately, we suggest our reflections will not only encourage other researchers to seek the input of hard-to-reach populations in justice, health, and policy contexts, but also to incorporate the experiences of underrepresented voices, elucidate findings and lessons learned from these unique populations, and engage in reflexive health communication and research strategies with highly stigmatized populations.